Environmentally relevant concentrations of methamphetamine and sertraline modify the behavior and life history traits of an aquatic invertebrate - Hossain, Md Shakhawate; Kubec, Jan; Grabicová, Katerina; Grabic, Roman; Randák, Tomas; Guo, Wei; Kouba, Antonín; Buřič, Miloš (Aquatic toxicology (Amsterdam, Netherlands), 2019)
Pharmaceutically active compounds are major contaminants of aquatic environments that show direct and indirect effects on aquatic organisms even at low concentrations. The aim of this study was to assess the effects of the illicit drug methamphetamine and the antidepressant sertraline on clonal marbled crayfish Procambarus virginalis. Crayfish exposed to the environmentally relevant concentrations of methamphetamine of ∼1 μg L-1 did not exhibit significant differences from unexposed controls in distance moved, velocity, and activity level with or without available shelter. Sertraline-exposed (∼1 μg L-1) crayfish were significantly more active, regardless of available shelter, and moved greater distances when shelter was available, compared to control crayfish. Crayfish exposed to methamphetamine and sertraline spent significantly more time outside the shelters compared to controls. Sertraline-exposed crayfish spawned more frequently and showed higher mortality than controls. The results suggest that the low environmental concentrations of the tested compounds could alter the behavior and life history traits of crayfish, resulting in higher reproductive effort and mortality.
Keywords: Behavior, Animal; Aquatic pollutants; bezobratlí; Sertraline; Crayfish; Aquatic Organisms; chemické látky znečišťující vodu; Invertebrates; sertralin; Behavior; Life Cycle Stages; Astacoidea; Water Pollutants, Chemical; Pharmaceuticals; zvířata; methamfetamin; Procambarus virginalis; vodní organismy; severní raci; chování zvířat; Life history traits; Methamphetamine; stadia vývoje; Animals